2018
DOI: 10.1002/jmv.25362
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sofosbuvir‐based therapy in hepatitis C virus recurrence post living donor liver transplant: A real life egyptian experience

Abstract: Background and Aim Direct acting antiviral has offered treatment of hepatitis C virus (HCV) recurrence post liver transplantation (LT) with an all‐oral regimen for short duration, excellent safety profile, and high sustained virological response (SVR). The aim of this study was to evaluate the efficacy and safety of sofosbuvir (SOF)‐based regimens in the real world among a cohort of Egyptian patients with recurrent HCV post living donor LT (LDLT). Methods Patients with HCV‐G4 recurrence post‐LDLT were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…These results are near to that obtained by Yosry et al [6], who found that, SVR12 was achieved in 94.7% in patients who received SOF/SMV for treatment of hepatitis C virus recurrence post living donor liver transplant.…”
Section: Figure (1)supporting
confidence: 79%
See 1 more Smart Citation
“…These results are near to that obtained by Yosry et al [6], who found that, SVR12 was achieved in 94.7% in patients who received SOF/SMV for treatment of hepatitis C virus recurrence post living donor liver transplant.…”
Section: Figure (1)supporting
confidence: 79%
“…Sofosbuvir has pan-genotypic effect on HCV with better pharmacokinetics and improved resistance profiles [5]. Sofosbuvir based DAAs are safe, effective, and well tolerated in patients with chronic hepatitis C patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a concern that a possible restoration of some of the immune cells after HCV clearance could also bear the risk of inducing unwanted sequelae including rejection episodes in the long-run (9,10,48). There is very limited literature that addressed the repercussions of HCV elimination on immune response in post-transplantation setting.…”
Section: Accepted Articlementioning
confidence: 99%
“…There has been a concern that a possible restoration of some of the immune cells after HCV clearance could also bear the risk of inducing unwanted sequelae, including rejection episodes in the long run. (9,10,48) There is limited literature that addresses the repercussions of HCV elimination on immune response in the posttransplantation setting. Importantly, we showed for the first time in this study that the therapy-induced clearance of HCV after LT does not significantly normalize a larger fraction of the altered inflammatory analytes in HCV + LT patients.…”
Section: Original Article | 897mentioning
confidence: 99%
“…SVR rates were as follow: 84.9% in SOF/RBV group, 94.7% in SOF/SIM, 100% in SOF/DCV, and 100% in SOF/LDV. Treatment was well tolerated with no significant drug-drug interactions [117]. The outcome of the combination SIM + SOF ± RBV in a group of liver transplant patients with HCV genotype 4 infection in Spain was evaluated in a real life study.…”
Section: Sofosbuvir/simeprevir (Sim)mentioning
confidence: 99%